Cosmic radiation backgrounds from primordial black holes. Issue 1 (29th September 2022) - Ziparo, F; Gallerani, S; Ferrara, A; Vito, F
ABSTRACT: Recent measurements of the cosmic X-ray background (CXB) and cosmic radio background (CRB) obtained with Chandra and ARCADE2 (Absolute Radiometer for Cosmology, Astrophysics, and Diffuse Emission) report signals in excess of those expected from known sources, suggesting the presence of a yet undiscovered population of emitters. We investigate the hypothesis that such excesses are due to primordial black holes (PBHs) that may constitute a substantial fraction of dark matter (DM). We present a novel semi-analytical model that predicts X-ray and radio emission due to gas accretion on to PBHs, assuming that they are distributed both inside DM haloes and in the intergalactic medium (IGM). Our model includes a self-consistent treatment of heating/ionization feedback on the surrounding environment. We find that (i) the emission from PBHs accreting in the IGM is subdominant at all times ($1{{\ \rm per\ cent}} \le I_{\rm IGM}/I_{\rm tot} \le 40{{\ \rm per\ cent}}$ ); (ii) most of the CXB/CRB emission comes from PBHs in DM mini-haloes ( M h ≤ 10 6 M⊙ ) at early epochs ($z$ > 6). While a small fraction ($f_{\rm PBH} \simeq 0.3{{\ \rm per\ cent}}$ ) of DM in the form of PBHs can account for the total observed CXB excess, the CRB one cannot be explained by PBHs. Our results set the strongest existing constraint on f PBH ≤ 3 × 10 −4 (30/ M PBH ) in the mass range of $1 \!-\! 1000 \, M_\odot$ . Finally, we comment on the implications of our results on the global H i 21 cm signal.